Microbial experimental evolution - Bennett, Albert F.; Hughes, Bradley S. (American journal of physiology. Regulatory, integrative and comparative physiology, 2009)
Microbes have been widely used in experimental evolutionary studies because they possess a variety of valuable traits that facilitate large-scale experimentation. Many replicated populations can be cultured in the laboratory simultaneously along with appropriate controls. Short generation times and large population sizes make microbes ideal experimental subjects, ensuring that many spontaneous mutations occur every generation and that adaptive variants can spread rapidly through a population. Another highly useful experimental feature is the ability to preserve and store ancestral and evolutionarily derived clones. These can be revived in parallel to allow the direct measurement of the competitive fitness of a descendant compared with its ancestor. The extent of adaptation can thereby be measured quantitatively and compared statistically by direct competition among derived groups and with the ancestor. Thus, fitness and adaptation need not be matters of qualitative speculation, but are quantitatively measurable variables in these systems. Replication allows the quantification of heterogeneity in responses to imposed selection and thereby statistical distinction between changes that are systematic responses to the selective regimen and those that are specific to individual populations.